TEORI POSITIVISME HANS KELSEN MEMPENGARUHI PERKEMBANGAN HUKUM DI INDONESIA (Lex Jurnalica, 2021)
Reflecting on legal theories in ancient times based on general political and philosophical theories. Meanwhile, modern legal theories are discussed in the language and thought systems of the jurists themselves. The difference lies in their method and emphasis. The legal theory of modern jurists is like the legal theory of the philosophers of scholastic teachings, based on the supreme belief whose inspiration comes from outside the realm of law itself. The growth of various schools in legal philosophy shows the constant struggle of thought in the field of legal science. If in the past, philosophy of law was a byproduct of philosophers, today its position is no longer like that because the problems of legal philosophy have become a separate subject of study for jurists. Posivism law for Hans Kelsen is to be cleaned of nonuridical elements, such as sociological, political, historical, and even ethical elements. This thought is known as pure legal theory. For him, the law is a necessity that regulates human behavior as a rational being. In Indonesia, law has a very broad scope, not limited to textuals in the form of statutory regulations. The functioning of the law in the midst of society does not only require laws but requires other things such as community culture, law enforcement officials and facilities and infrastructure. From this we can see that the positivism school tries to imprison the law only as a textual one.